L’engagement des femmes entre émancipations et dominations. Le cas de radio Lorraine Cœur d’Acier, Longwy, 1979-1980 - Ingrid Hayes (Genre & Histoire)
In 1979-1980 in Longwy (Lorraine region), the French trade union, the CGT, established the Lorraine Cœur d’Acier (LCA) radio, following mobilizations in defense of the steel industry. The radio opened unusual opportunities for some women to express themselves and to become politicized in a particularly masculine professional and militant sector. Women’s positions in the LCA were, however, ambivalent. Although gender operated to marginalize them, some were able to resist and even to challenge the male radio operators. Women’s experiences varied depending on their social class and their activist background. Some of the women involved were members of communist groups (both the CGT and the PCF) ; others shared a cultural background and a militant history that had emerged in the wake of 1968. A third group included wives of steel workers for whom the radio was their first militant experience. This latter group was less able to challenge gender typing, but their experiences within the radio had a more destabilizing effect on them, producing a form of politicization rooted in locality and relatively distant from organized politics.